Understanding the defense mechanism of Allium plants through the onion isoallicin-omics study - Cho, Heejung; Park, Ji Yeon; Kim, Duck Hyun; Han, JiWon; Natesan, Karthi; Choi, Min-Seon; Lee, Seon-Kyeong; Kim, Jiseon; Cho, Kun; Ahn, Byoung Ohg (Frontiers in Plant Science, 2024)
Onion (Allium cepa L.) is an important seasoning vegetable worldwide. It belongs to the Allium genus, which produces distinctive flavor compounds, allicin/isoallicin. It has been known that allicin/isoallicin is produced upon cell damage by vacuole-localized alliinase releasing. Pungent isoallicin and lachrymaroty factor (LF) are unique features of onions. To understand the isoallicin system of onions, we identified and characterized the biosynthesis-related genes by displaying transcriptional profiles and analyzing the isoallicin contents of onion plants. The DHW30006 onion genome encoded 64 alliinase (ALL) and 29 LF synthase (LFS) proteins, which are the key enzymes for producing of isoallicin and LF. Interestingly, when we analyzed the N-terminal signal peptide sequences (SP) necessary for transport to the vacuole, we found that 14 ALLs contained the SP (SP-ALL) and 50 ALLs did not (non-SP-ALL). We hypothesized that non-SP-ALLs stayed in the cytosol of onion cells, reacted with isoalliin, and generated isoallicin without cell damage. Our transcriptome and LC-MS/MS analyses reveal that isoallicin levels vary significantly across onion tissues and growth stages, with substantial production occurring in intact cells through cytosolic alliinases and an increase through vacuolar alliinases upon tissue disruption. This novel observation suggests that the isoallicin system in onions functions as a dual-defense mechanism: cytosolic alliinases maintain a constant level of defense against biotic stress in undamaged tissues, while vacuolar alliinases enhance isoallicin production in response to tissue damage by herbivory and insects. Together, these coordinated mechanisms demonstrate an adaptable and dynamic defense strategy against biotic stresses in Allium plants.